Life Cycle Analysis in the Context of Smart Cities - Berville Charles; Croitoru Cristiana; Bode Florin (E3S Web of Conferences)
The transformation of urban areas into smart cities integrates advanced technologies to enhance efficiency, sustainability and liveability. In this study, we employed a systematic literature review methodology to assess the environmental impacts of smart city initiatives. We applied strict inclusion and exclusion criteria to ensure the relevance and quality of the selected studies and conducted a qualitative content analysis to extract and synthesize key findings related to Life Cycle Assessment (LCA) and sustainability in the context of smart cities. Key benefits of smart cities include improved energy efficiency through smart grids and energy-efficient buildings, reduced emissions from smart transportation and electric vehicles, optimized water and waste management and data-driven urban planning. While smart cities rely on ICT for enhanced efficiency, data collection and processing must be done responsibly to limit the environmental impact of data centers and network infrastructure. This can be achieved through edge computing, energy-efficient data centers, and policies that promote digital sobriety. However, challenges such as the high energy use of ICT infrastructure, electronic waste, construction impacts, data privacy, cybersecurity risks and the digital divide are significant. Strategies to mitigate these include integrating sobriety, promoting a circular economy, stakeholder engagement and robust policy frameworks.